THERMAL STABILITY OF THE Cu-CeO2 INTERFACE ON SILICA AND ALUMINA, AND ITS RELATION WITH ACTIVITY IN THE OXIDATION REACTION OF CO AND THE DECOMPOSITION OF N2O - Alvarez, Pablo; Aguila, Gonzalo; Guerrero, Sichem; Araya, Paulo (Journal of the Chilean Chemical Society, 2018)
The effect of the support on the formation of the Cu-CeO2 interface and its thermal stability after calcination at 500, 700 and 900 ºC is studied. The supports used are SiO2, because of its inert character, and Al2O3, because it can interact with the Cu and Ce species on the surface. The catalysts were characterized by BET, XRD, UV-vis DRS, and TPR with H2. The catalytic activity in the CO oxidation reactions with O2 at low temperature and the decomposition of N2O were selected to visualize the effect of temperature on the concentration of Cu-CeO2 interfacial sites. The results show that at a calcination temperature of 500 ºC the formation of the Cu-CeO2 interface is favored over the SiO2 support. However, the stability of the Cu-CeO2 interface on SiO2 is much lower than on Al2O3, causing a substantial decrease of the interfacial sites calcining at 700 ºC, and segregation of the Cu and Ce species on the surface of the silica, with complete loss of the catalytic activity in both reactions when calcining at 900 ºC. In contrast, on alumina the Cu-CeO2 interface is more stable and presents a significant catalytic activity in both reactions, even when calcining at 900 ºC. The characterization results show that the sintering process of Cu species and CeO2 particles is less on the alumina support due to the greater interaction of the Cu and Ce with this support.